Position, shape and anatomic variations of the mental foramen evaluated by cone beam computed tomography. - Vinatea Cuenca de Figueroa, María Teresa (2022)
Objective: To evaluate the position, shape and anatomical variants of the mental foramen evaluated by cone beam computed tomography in patients of the dental radiology service of the Cayetano Heredia Hospital. Material and Methods: All the CT scans acquired between the years 2017 and 2020 that met the selection criteria were evaluated and the mentioned variables were analyzed. Observations were recorded on a data sheet designed for this purpose. Results: 117 tomographic volumes were evaluated, adding a total of 209 mental foramina. The most common horizontal and vertical position was between the first and second premolars and below the imaginary line of the premolars respectively. The oval horizontal and rounded forms were presented in similar percentages. The most frequently found anatomical variant was the lateral lingual foramen. Conclusions: No statistically significant association was found between the position, shape and anatomical variants of the mental foramen with sex, age and side.